Ligth ions and ozone - generaion and interactions with living organisms - Kříha, V.; Aubrecht, L. (Вопросы атомной науки и техники, 2005)
With directly in the living organism born ions exception, LNI coming through three phases: ionisation, attachment by the electronegative molecules and the clusters formation due to local electrostatic interactions. The quantitative analysis of physical parameters leads to conclusion that we cannot find any physical property (till known) explaining the positive affect of LNI on living organisms. Analysis of possible mechanism produces several hypotheses of LNI-organism interaction. A simplified semi-quantitative model of respiratory tract was developed for estimation of ions and ozone interaction with living organisms. A formation of oxygen radicals and products of their chain-reactions in intrinsic conditions is discussed. Обговорюються можливі механізми взаємодії легких іонів з живими організмами. Легкі негативні іони (ЛНІ) при проходженні через живі організми проходять через 3 фази: іонізація, захоплення електронегативними молекулами й утворення кластерів унаслідок локальних електростатичних взаємодій. Кількісний аналіз фізичних параметрів приводить до висновку, що жодне з відомих фізичних властивостей не може пояснити позитивний вплив ЛНІ на живі організми. Аналіз можливих механізмів народжує декілька гіпотез взаємодії ЛНІ – організм. Розвито спрощену напівкількісну модель респіраторного тракту для оцінки взаємодії іонів і озону з живими організмами. Обговорюється утворення кисневих радикалів і продуктів їхніх ланцюгових реакцій. Обсуждаются возможные механизмы взаимодействия лёгких ионов с живыми организмами. Лёгкие отрицательные ионы (ЛОИ) при прохождении через живые организмы проходят через 3 фазы: ионизация, захват электроотрицательными молекулами и образование кластеров вследствие локальных электростатических взаимодействий. Количественный анализ физических параметров приводит к выводу, что ни одно из известных физических свойств не может объяснить положительное влияние ЛОИ на живые организмы. Анализ возможных механизмов рождает несколько гипотез взаимодействия ЛОИ – организм. Развита упрощённая полуколичественная модель респираторного тракта для оценки взаимодействия ионов и озона с живыми организмами. Обсуждается образование кислородных радикалов и продуктов их цепных реакций.